2018
DOI: 10.1017/s0714980818000302
|View full text |Cite
|
Sign up to set email alerts
|

Senior Centres in Canada and the United States: A Scoping Review

Abstract: Senior centres have been identified as a "focal point" for delivering services to the rapidly growing older adult populations in Canada and the United States. Despite this important role, academic research studying senior centres has been limited. This scoping review identified English-language empirical research studies focusing on senior centres that were published in an academic journal in 2000 or later. A total of 58 studies were identified (n = 51 American and n = 7 Canadian). The majority of the articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 63 publications
2
27
1
2
Order By: Relevance
“…The many Asian, Latinx, Black/African American, and first-generation immigrant older adults challenges senior centers to design programs that are culturally relevant and appeal to this diverse clientele. As noted in previous studies, a majority of senior center participants (66.6%) are currently single (never married, divorced, separated, or widowed) and half (50.3%) live alone (Kadowaki & Mahmood, 2018;Pardasani, 2010Pardasani, , 2019Pardasani & Sackman, 2014;Turner, 2004). This highlights how senior centers might be a source of socialization and companionship for participants.…”
Section: Senior Center Members and Nonmemberssupporting
confidence: 65%
See 3 more Smart Citations
“…The many Asian, Latinx, Black/African American, and first-generation immigrant older adults challenges senior centers to design programs that are culturally relevant and appeal to this diverse clientele. As noted in previous studies, a majority of senior center participants (66.6%) are currently single (never married, divorced, separated, or widowed) and half (50.3%) live alone (Kadowaki & Mahmood, 2018;Pardasani, 2010Pardasani, , 2019Pardasani & Sackman, 2014;Turner, 2004). This highlights how senior centers might be a source of socialization and companionship for participants.…”
Section: Senior Center Members and Nonmemberssupporting
confidence: 65%
“…Studies conducted over several decades have consistently found that senior center members tend to be older women who were never married or are widowed, with medium to low incomes, and minimal physical disabilities (Calsyn & Winter, 2000;Krout, 1998;Pardasani, 2004b;Turner, 2004). The average age of senior center members has been increasing over the years, raising concern that younger seniors are not using these services (Kadowaki & Mahmood, 2018;Krout, 1998;Pardasani, 2004bPardasani, , 2010Pardasani & Sackman, 2014;Turner, 2004;Walker et al, 2004). This trend has shown no signs of reversal in the last two decades.…”
Section: Characteristics Of Senior Center Membersmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated by two recent reviews, the existing literature has mainly focused on what happens inside the senior center but there is a lack of information about seniors' lives beyond the center [33] and more research on the individual effects of senior center attendance is needed [34]. With the notable exception of Turner et al [35], who used pedometers to measure seniors' weekly physical activity, to our knowledge no other study has used a device-based measurement of physical activity.…”
Section: Introductionmentioning
confidence: 99%